The China-Russia relationship and the creation of the culture of the Shanghai Cooperation Organization - Machado, Diogo (2021)
This article seeks to understand how the relationship between China and Russia, the two most influential members in the creation and action of the Shanghai Cooperation Organization, influenced the organization's culture. Through constructivist research, the main inter subjectively shared elements in the referred relationship are identified. It is argued that they were incorporated into the culture of the Shanghai Cooperation Organization, especially in terms of formal rules and norms.